Effect of rifampicin and CYP2B6 genotype on long-term efavirenz autoinduction and plasma exposure in HIV patients with or without tuberculosis - Ngaimisi, Eliford; Mugusi, S.; Minzi, O.; Sasi, P.; Riedel, Klaus-Dieter; Suda, A.; Ueda, N.; Janabi, M.; Mugusi, F.; Haefeli, Walter E.; Bertilsson, L.; Burhenne, Jürgen; et al. (Clinical pharmacology & therapeutics, 2011)
We performed a prospective comparative study to examine, from a pharmacogenetics perspective, the effect of rifampicin (RIF) on long-term efavirenz (EFV) autoinduction and kinetics. In a study population of patients with HIV receiving EFV with RIF (arm 2, n = 54) or without RIF (arm 1, n = 128 controls), intraindividual and interindividual plasma EFV and 8-hydroxyefavirenz levels were compared at weeks 4 and 16 of EFV therapy. In arm 2, RIF was initiated 4 weeks before starting EFV. In controls (arm 1), the plasma EFV was significantly lower whereas 8-hydroxyefavirenz was higher at week 16 as compared to week 4. By contrast, there were no significant differences in plasma EFV and 8-hydroxyefavirenz concentrations over time in arm 2. At week 4, the plasma EFV concentration was significantly lower in arm 2 as compared to arm 1, but no significant differences were observed by week 16. When stratified by CYP2B6 genotype, significant differences were observed only with respect to CYP2B6*1/*1 genotypes. Ours is the first report of the CYP2B6 genotype-dependent effect of RIF on long-term EFV autoinduction. Clinical Pharmacology & Therapeutics (2011) 90 3, 406-413. doi:10.1038/clpt.2011.129
Gesehen am 22.09.2022